DIFERENCIAÇÃO GENÉTICA DE MORFOTIPOS DE Cecropia pachystachya TRÉCUL (URTICACEAE) - Santos, Jhonnatan de Oliveira (2019)
Brazil has six biomes with distinct characteristics, Amazonia, Caatinga, Cerrado, Atlantic Forest, Pampa and Pantanal. These have several vegetation formations, which allows high diversity of habitats and species. The biomes have different evolutionary histories, which allowed the composition of species different from each other. However, they undergo intense devastation over the years, losing part of their biodiversity, necessitating conservation efforts. For this, however, one must first know their species. Some of the species that occur in the majority of Brazilian biomes belong to the genus Cecropia Loefl. Among these, Cecropia pachystachya Trécul, known as the white embaúba. This species has controversial circumscription. Due to the high morphological differentiation along its distribution in Brazil, the species has already been divided into five species (C. pachystachya, C. digitata Klotzsch, C. lyratiloba Miq., C. catarinensis Cuatrec., C. adenopus Mart. ex Miq.). Synonymization was based on the hypothesis that the morphological variations are due to the phenotypic plasticity of the species. There are no studies evaluating whether these morphological differences also occur at the molecular level. Thus, the objective of this work was to evaluate if the morphological differences observed in C. pachystachya also occur at the molecular level. To reach the objectives, 18 accessions of the species belonging to five morphotypes were collected in the typical locations of each morphotype and evaluated. Two species were collected in the Amazon biome (morphotype C. adenopus), two in the Caatinga (morphotype C. digitata), four in the Cerrado (morphotype C. digitata), and 10 in the Atlantic Forest (two of the morphotype C. pachystachya senso stricto, five C. lyratiloba and three C. catarinensis). The trnL (chloroplast) and ITS (nuclear) regions of each access were sequenced and used for the construction of genetic relation trees based on the methods of Maximum Parsimony (MP) and Bayesian Inference (BI). Two accessions of C. hololeuca Miq. were used as outgroup. All sequences obtained were homologous with sequences of C. pachystachya deposited in GeneBank. The accesses formed two large groups with strong support, the first with accesses from the Amazon, Caatinga and Cerrado (ACC group), and the second with accesses from the Atlantic Forest (MA group). The ACC group was divided into two subgroups: the Amazon subgroup and the Caatinga / Cerrado subgroup. The MA group was divided into three subgroups: North Atlantic Forest, Central Atlantic Forest and South Atlantic Forest. The separation of the ACC and MA groups seems to be related to the evolutionary history of the biomes where the specimens were collected. It is believed that in the past, in the interglacial periods, the Amazon has advanced to regions where the Caatinga and Cerrado are today, justifying the grouping of the accesses coming from these biomes along with the accesses of the Amazon. On the other hand, the formation of the subgroups is possibly related to climatic changes that occurred in the last ice ages, and the presence of the Pleistocene refuges as well as the climatic conditions differentiated within and between the biomes that settled after the last glacial maximum. In this sense, the division of the subgroups according to the distribution of the climate may reflect adaptations of the accesses to the climatic conditions to which they are exposed. The division of the MA group may be related to the connection routes to the Amazon during the past. The clustering of the accessions studied, obtained with the genetic data, according to the morphotype shows that the differences observed in C. pachystachya are not only phenotypic plasticity. Thus, morphological analysis of the morphotypes is recommended, so that, in combination with molecular data, it reestablishes the morphotypes of C. pachystachya as species. The reestablishment of the species may have implications on the conservation status of species of the genus Cecropia in Brazil.